2018
DOI: 10.1093/hmg/ddy313
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Grainyhead-like 3 causes spina bifida and interacts genetically with mutant alleles of Grhl2 and Vangl2 in mice

Abstract: The genetic basis of human neural tube defects (NTDs), such as anencephaly and spina bifida (SB), is complex and heterogeneous. Grainyhead-like genes represent candidates for involvement in NTDs based on the presence of SB and exencephaly in mice carrying loss-of-function alleles of Grhl2 or Grhl3. We found that reinstatement of Grhl3 expression, by bacterial artificial chromosome (BAC)-mediated transgenesis, prevents SB in Grhl3-null embryos, as in the Grhl3 hypomorphic curly tail strain. Notably, however, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 46 publications
(89 reference statements)
1
37
2
Order By: Relevance
“…In vertebrates, Grainyhead-like orthologues display a conserved functional homology of regulating processes, required for epithelial development. Studies in mice [2,5], Xenopus [6] and zebrafish [7] have determined remarkable conserved functional homology to Drosophila grh , apparent in the morphogenic development of the epidermal barrier [8,9,10,11], closure of the neural tube [12,13,14,15], maintenance of neural cell survival [16], and the growth and development of the craniofacial skeleton [17,18]. Together, these findings point to a critical role for Grhl function in the development of all organisms within the animal kingdom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrates, Grainyhead-like orthologues display a conserved functional homology of regulating processes, required for epithelial development. Studies in mice [2,5], Xenopus [6] and zebrafish [7] have determined remarkable conserved functional homology to Drosophila grh , apparent in the morphogenic development of the epidermal barrier [8,9,10,11], closure of the neural tube [12,13,14,15], maintenance of neural cell survival [16], and the growth and development of the craniofacial skeleton [17,18]. Together, these findings point to a critical role for Grhl function in the development of all organisms within the animal kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of human Grainyhead-like ( Grhl ) orthologues have begun to uncover the role that loss of function or gene variants have in adult-onset diseases, such as hearing loss/deafness [22,23], defects of epidermal integrity and, particularly, numerous forms of cancer [9,24,25,26]. The Grhl -genes are also implicated in the aetiology of a number of human diseases, including cleft palate [27,28], spina bifida [5,14,29], cancer [30], ectodermal dysplasia [28] and asthma [31]. This incredible functional diversity is mediated, at least in part, through a grh / Grhl transcription factor binding to a promoter or enhancer element and regulating the subsequent transactivation or repression of target effector genes through recruitment of transcriptional co-factors.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the potential pathogenic role of the rare and novel missense CLDN variants identified in NTD patients, we used an overexpression assay in the chick embryo model to examine the effect of these variants on neural tube closure. Previous studies have shown that knockdown or overexpression of NTD-related genes can lead to similar NTD phenotypes (Ting et al, 2003;Yu et al, 2006;Gustavsson et al, 2007;De Castro et al, 2018). The chick embryo is an excellent model to study neural tube closure for several reasons: (1) the tissue and cellular behaviors that regulate neurulation in the chick have been well-studied, (2) the morphogenetic movements regulating neural tube closure in chick and human embryos are predicted to be very similar, (3) neural tube closure occurs over a short period of time (∼28 h) making it easy to collect a large number of embryos (Schoenwolf and Franks, 1984;Smith and Schoenwolf, 1987;Schoenwolf et al, 1988;Schoenwolf and Alvarez, 1989;Schoenwolf, 1991;Smith et al, 1994;Moury and Schoenwolf, 1995;Sausedo et al, 1997;Lawson et al, 2001;Kinoshita et al, 2008;Nishimura et al, 2012;Chen et al, 2017), and (4) the neural tube is easily accessible for manipulation in ex ovo culture.…”
Section: Overexpressing Cldn3 Cldn8 and Cldn19 Variants Cause Open mentioning
confidence: 99%
“…Evidence from animal studies has suggested that Grhl3 is a component of the PCP pathway, which functions as a key transcriptional regulator (Caddy et al, ). It interacts genetically with Vangl2 in epidermal healing and neural tube closure (De Castro, Gustavsson, et al, ; Dworkin, Jane, & Darido, ). In an animal study, Ting et al () found that all Grhl3 knockout mice embryos displayed full penetrance with spina bifida and curled tail, caused by a primary failure of neural tube closure.…”
Section: Introductionmentioning
confidence: 99%